Non-Fossil Methane Emissions Mitigation From Agricultural Sector and Its Impact on Sustainable Development Goals - Sirigina, Devesh Sathya Sri Sairam; Nazir, Shareq Mohd (Frontiers in Chemical Engineering, 2022)
Agriculture sector contributes to ~40% of methane emissions globally. Methane is also 28 times (Assessment Report 5) more potent greenhouse gas than CO2. In this work, we assess the impact from measures for mitigating methane emissions from agricultural sector on the achievement of all the 17 United Nations’ Sustainable Development Goals (SDGs). A keyword literature review was employed that focused on finding the synergies and trade-offs with non-fossil methane emissions from agricultural sector and respective SDGs’ targets. The results were in broad consensus with the literature aimed at finding relationship between SDGs and measures targeting climate change. There is a total of 88 synergies against 8 trade-offs from the 126 SDGs’ targets that were assessed. It clearly shows that measures to mitigate methane emissions from agricultural sector will significantly help in achieving the SDGs. Since agriculture is the primary occupation and the source of income in developing countries, it can further be inferred that methane mitigation measures in developing countries will play a larger role in achieving SDGs. Measures to mitigate methane emissions reduces poverty; diversifies the source of income; promotes health, equality, education, sanitation, sustainable development while providing energy and resource security to the future generations.